Professional Pedagogical Activity and its Current Problems - Pulatjon Makhsudovich Makhsudov (Genius Journals, 2022)
The article is devoted to professional and pedagogical activity and its topical issues. The article talks about the professional and pedagogical activity of a vocational education teacher and its peculiar features, about the training of a vocational education teacher in higher educational institutions, about the structural model of a modern vocational education teacher.
Keywords: Vocational education; professional and pedagogical activity; vocational training teacher; methodological activity